Evaluation of motivation and job satisfaction in the peasant fight savings-credit cooperative - Alcívar-Martínez, Benigno Javier (2023)
The present study was carried out with the objective of evaluating the motivation and its contribution to the job satisfaction of the staff of the Cooperativa AhorroCrédito Lucha Campesina, being necessary to identify the existing variables in the environment, knowing the current state of motivation that the employees were in, in order to know their contribution to job satisfaction. The methods used were inductive, deductive, descriptive, these allowing to collect all the pertinent information, necessary for the execution and fulfillment of the proposed objectives, these being supported by the techniques of observation, interview and surveys to the personnel that works in the cooperative The results allowed propose an action plan that will strengthen the indicators that were found to have shortcomings in the study variables. Taking into account that the institution has an acceptable motivation, presenting small deficiencies in five indicators within the variables studied